Two-Step Purification of L-Asparaginase from Acrylaway® L - Louise Lacalendola Tundisi; Diego de Freitas Coêlho; Alessandra Valéria de Sousa Faria; Adalberto Pessoa Junior; Elias Basile Tambourgi; Laura de Oliveira Nascimento; Edgar Silveira; Priscila Gava Mazzola (Universidade de São Paulo, 2022)
Abstract L-Asparaginase (L-ASNase) is a biopharmaceutical used for acute lymphoblastic leukaemia (ALL) treatment, dramatically increasing the patients' chance of cure. However, its production and distribution in developing countries were disrupted because of its low profitability, which caused great concern among patients. This study evaluates the feasibility of combining fractional precipitation and aqueous two-phase systems (ATPS) to purify L-ASNase from a low-grade product, commercially known as Acrylaway® L. The ATPS purification results were not particularly expressive compared to the two-step purification process composed of ethanol precipitation and gel filtration, which was able to recover the target molecule with a purification factor over 5 fold. Thus, we studied a purification process capable of manufacturing pharmaceutical grade L-ASNase from a commercially available low-grade raw material; however, improvements regarding its throughput must be achieved, and high purity is the first step to apply it as a new biopharmaceutical product. The proposed process could pose as a short-time solution to mitigate its shortage while a cost-effective production plant is being developed.